Modernidades religiosas latinoamericanas. Un renovado debate epistemológico y conceptual - Fortunato Mallimaci (Caravelle)
In this paper we carry on a reflection about how the “world” of Latin-American and Caribbean present beliefs and social-religious groups is analyzed, explained and interpreted. A new epistemological approach must recognize a hermeneutics which feeds upon the actors themselves and questions colonial paradigms. Indeed, capitalism has reconfigurated various religious modernities of which the Latin-American one is just one among others. This demands new categories to redefine concepts such as secularisation and secularity, and to reinterpret the narrow relations built in the continent between politics, culture, body, the economic aspect and the symbolic one, and the State above all.